Genetic and Genomic Resources for Improving Biotic Stress Tolerance in Chickpea - Kumar, Tapan; Tiwari, Neha; Saxena, Deep R.; Istanbuli, Tawffiq; Hamwieh, Aladdin (Springer, 2024)
Chickpea, a fundamental member of the legume family, stands out as a vital crop with an intriguing genetic makeup. With a genome size of approximately 738 Mbp, this crop boasts a cool-season preference and self-pollinating tendencies. Notably, chickpea demonstrates remarkable resilience in regions characterized by scarce rainfall and high temperatures. The nutritional prowess of chickpea is a beacon of hope against malnutrition, particularly for communities residing in hot, drought-prone arid and semiarid regions across South Asia and Africa. In these challenging environments, chickpea has emerged as a superior crop, addressing nutritional deficiencies and supporting livelihoods. Diving into chickpea’s genetic diversity reveals a wide spectrum of genotypic and phenotypic variations, including robust tolerance to both abiotic and biotic stresses. Traditional breeding approaches aimed at bolstering stress resistance have garnered substantial success. However, recent years have witnessed the emergence of innovative strategies, such as functional genomics and molecular breeding, targeting increased yields under adverse environmental conditions. The prospect of leveraging genomic tools to further enhance chickpea’s performance remains abundant. The utilization of DNA-based markers, including Kompetitive allele specific PCR (KASP), Diversity Arrays Technology (DArT), expressed sequence tag-derived simple sequence repeat markers (EST-SSRs), and single-strand conformational polymorphism-single nucleotide polymorphism (SSCP-SNP), plays a pivotal role. These markers not only shed light on population structure and genetic diversity but also serve as crucial instruments for expedited and precise crop improvement strategies. The foundation of molecular marker-based genetic linkage maps and the identification of genomic regions responsible for yield under biotic stresses, particularly Fusarium wilt (FW), have paved the way for marker-assisted selection and breeding of chickpea cultivars. In conclusion, this review encapsulates the journey of exploring chickpea’s genetic and genomic resources. These endeavors are geared toward elevating both abiotic and biotic stress resistances, culminating in the development of cultivars that stand superior in their stress tolerance. Chickpea’s enduring legacy as a resilient and nutritionally rich crop is poised to make a lasting impact on global agriculture and food security.